Opto-VLSI-Based Beamformer for Radio-Frequency Phased-Array Antennas - Feng Xiao; Budi Juswardy; Kamal Alameh; Shilin Xiao; Weisheng Hu (IEEE Photonics Journal, 2012)
An Opto-VLSI-based tunable beamformer for radio frequency (RF) smart antennas is reported and its concept is demonstrated. RF beam steering is achieved by uploading appropriate phase holograms onto the Opto-VLSI processor so that RF true-time delays (TTDs) are independently generated for each element of the antenna array by simply using several erbium-doped fiber amplifier (EDFA) loops to realize independent tunable fiber lasers in conjunction with a dispersive optical fiber. Experimental results demonstrate RF beam steering up to 30° with a 4-element linear patch antenna array operating at 1.85 GHz.